STUDI EKSPERIMENTAL PEMBUATAN BAHAN BAKAR DARI LIMBAH PLASTIK LDPE DENGAN PROSES PIROLISIS TERMAL DAN KATALITIK (ZEOLIT ALAM & Y) SERTA UJI PERFORMANSI MESIN DIESEL - , PRABUDITYA BHISMA WISNU WARDHANA, Prof. Dr. Ing. Ir. Harwin Saptoadi, M.SE. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Plastic production increased along with the growth of the world population. Plastic is very popular because it has many advantages compared to other materials. This phenomenon will result in the increase of plastic waste generated. Processing by means of incineration will cause considerable side effects harmful to health. The need for plastic waste management is a serious concern for the preservation of the environment. The most topical issue these days about the depletion of petroleum resources. This is compounded by the lifestyle of the people who are still quite dependent on the presence of petroleum in addition to non optimal use of alternative fuels. This study will try to develop a method of processing plastic waste by means of pyrolysis. Pyrolysis method to be used is the combination of thermal and catalytic pyrolysis method. The raw material used is plastic waste that kind of LDPE (Low Density Polyethylene). Catalytic pyrolysis using natural zeolite catalyst and zeolite Y. Pyrolysis reactor in this study using a fixed batch reactor. Products of this plastic waste pyrolysis oil will be blended with biodiesel Pertamina and tested on diesel engines to determine the performance and emissions produced. Waste plastic pyrolysis method produces liquid products, solid and gas. Catalytic pyrolysis process takes a relatively shorter than the thermal pyrolysis. The results show that the performance and emissions produced by pyrolysis fuel oil-biodiesel mixture is not much different from the use of pure biodiesel. diesel engine test results showed that the plastic waste pyrolysis oil has great potential to become an alternative fuel in the future.